Prognostic Markers for Poor Recovery After Mild Traumatic Brain Injury in Older Adults: A Pilot Cohort Study. Issue 6 (November 2016) - Kristman, Vicki L.; Brison, Robert J.; Bédard, Michel; Reguly, Paula; Chisholm, Shelley
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To identify prognostic markers associated with poor recovery from mild traumatic brain injury (MTBI) in older adults. Setting: Three Ontario emergency departments. Participants: Forty-nine participants aged 65 years and older that visited an emergency department for MTBI. Design: Pilot prospective cohort study. Main Measures: Recovery from MTBI determined using the Rivermead Postconcussion symptom Questionnaire, the Glasgow Outcomes Scale—Extended, physical and mental health functioning (SF-12), and a single question on self-rated recovery assessed by telephone shortly after emergency department visit (baseline) and again 6 months later. Predictors were measured at baseline. Results: Markers potentially associated with poor recovery included reporting worse health 1 year before the injury, poor expectations for recovery, depression, and fatigue. Conclusion: Recovery after MTBI in older adults may be associated more with psychosocial than with biomedical or injury-related factors.